2013
DOI: 10.1186/1745-6673-8-18
|View full text |Cite
|
Sign up to set email alerts
|

Solving a methodological challenge in work stress evaluation with the Stress Assessment and Research Toolkit (StART): a study protocol

Abstract: BackgroundStress evaluation is a field of strong interest and challenging due to several methodological aspects in the evaluation process. The aim of this study is to propose a study protocol to test a new method (i.e., the Stress Assessment and Research Toolkit) to assess psychosocial risk factors at work.DesignThis method addresses several methodological issues (e.g., subjective vs. objective, qualitative vs quantitative data) by assessing work-related stressors using different kinds of data: i) organisation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 39 publications
0
14
0
2
Order By: Relevance
“…In the previous literature, absenteeism has often been studied subjectively, but the use of different kinds of measures is recommended in stress evaluation research, as investigating psychosocial risk factors using only subjective or objective measures could produce biased results, for example from personal interpretations of risk factors (Guglielmi et al 2013). In addition, Lidwall et al (2009) postulated that, in studies aimed at investigating the relationship between work-family interference and sickness absence, both objective and subjective measures should be considered.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In the previous literature, absenteeism has often been studied subjectively, but the use of different kinds of measures is recommended in stress evaluation research, as investigating psychosocial risk factors using only subjective or objective measures could produce biased results, for example from personal interpretations of risk factors (Guglielmi et al 2013). In addition, Lidwall et al (2009) postulated that, in studies aimed at investigating the relationship between work-family interference and sickness absence, both objective and subjective measures should be considered.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…A common criticism concerning studies on occupational mental health refers to the fact that most empirical studies rely on self-reported measures both of independent and outcome variables [6,[29][30][31][32][33][34]. Therefore, individuals in identical jobs can rate the amount of job stress or, specifically, work-related conflict quite differently.…”
Section: Introductionmentioning
confidence: 99%
“…Die Beschreibung von Messinstrumenten für psychosoziale Belastungsfaktoren am Arbeitsplatz, nimmt einen großen Raum in der Literatur zu Gefährdungsbeurteilungen ein [23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Messinstrumente, die zur Messung psychosozialer Belastungsfaktoren am Arbeitsplatz eingesetzt werden, lassen sich durch verschiedene Merkmale voneinander unterscheiden.…”
Section: Wie Werden Psychische Belastungen Am Arbeitsplatz Gemessen?unclassified
“…Objektive Beobachtungsverfahren sind in der Regel aufwendig und können nur einen kleinen Anteil von Arbeitsplätzen erfassen, während subjektive Fragebögen von vielen Beschäftigten an vielen Arbeitsplätzen ausgefüllt werden können. Durch Kombination subjektiver und objektiver Verfahren lassen sich mögliche Messfehler reduzieren [24].…”
Section: Wie Werden Psychische Belastungen Am Arbeitsplatz Gemessen?unclassified